2016
DOI: 10.1128/jcm.02289-15
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Genotypic Review of Carbapenemase-Producing Organisms in British Columbia, Canada, between 2008 and 2014

Abstract: pneumoniae isolates lack clonality, although some seemingly related clusters have been found. Plasmid analysis showed evidence of the spread of plasmids carrying carbapenemase-encoding genes between the examined isolates. Analysis of Enterobacter cloacae isolates revealed a more clonal nature of these CPOs in BC. The presence of related clusters provides evidence of interpatient organism transmission both within and between institutions. Although in our study, NDM-harboring E. cloacae isolates appeared to spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Recent studies in 2 provinces showed that 40% of patients in Ontario and 44% of patients in British Columbia identified as CPE colonized or infected had no history of hospitalization outside of Canada or of high-risk travel. 8,9,17 In Ontario, most of these patients (including 55% and 67% of all patients with KPC-and VIM-producers, respectively) had been hospitalized in Canada. 9 Despite these data suggesting acquisition and transmission of CPE in local hospitals, and recent studies reporting that transmission control programs which include screening patients with a history of local healthcare only is cost-effective in low-prevalence settings, 18,19 only 17% and 21% of the hospitals surveyed screened patients if they had a history of hospitalization in Ontario and in Canada outside of Ontario, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in 2 provinces showed that 40% of patients in Ontario and 44% of patients in British Columbia identified as CPE colonized or infected had no history of hospitalization outside of Canada or of high-risk travel. 8,9,17 In Ontario, most of these patients (including 55% and 67% of all patients with KPC-and VIM-producers, respectively) had been hospitalized in Canada. 9 Despite these data suggesting acquisition and transmission of CPE in local hospitals, and recent studies reporting that transmission control programs which include screening patients with a history of local healthcare only is cost-effective in low-prevalence settings, 18,19 only 17% and 21% of the hospitals surveyed screened patients if they had a history of hospitalization in Ontario and in Canada outside of Ontario, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the incidence of carbapenemase-producing Acinetobacter spp was also determined to be low and mostly confined to two clustered outbreaks of isolates containing OXA-235 enzymes; however, there is evidence that the overall number of carbapenemaseproducing pathogens may be on the rise. 32,33 A single-center study from Turkey found that from 2012 to 2015 there was an increase in XDR-A. baumannii infections from 52.4 to 71.7% but the trend in XDR-Klebsiella spp remained stable.…”
Section: Epidemiology Of Gram-negative Resistance In Intensive Care Umentioning
confidence: 99%
“…Although the reasons are currently unclear, some clusters of CPOs show highly clonal PFGE patterns, whereas others show great diversity, but when plasmid RFLP methods are applied, the clonality of the plasmids identify clusters of highly diverse bacteria harboring the same plasmid and, in some cases, bacteria of different genera and species. 23 Fragmenting the pathogen genome can also be accomplished by PCR. One example is repetitive-element PCR (rep-PCR), which is the foundation for DiversiLab (bioMérieux, Marcy l'Etoile, France), a semiautomated method, which is used in many hospital settings to investigate clusters and outbreaks of infectious diseases.…”
Section: Molecular Epidemiologymentioning
confidence: 99%